2015
DOI: 10.3402/meo.v20.28627
|View full text |Cite
|
Sign up to set email alerts
|

Tools to investigate how interprofessional education activities link to competencies

Abstract: Integrating interprofessional education (IPE) activities and curricular components in health professions education has been emphasized recently by the inclusion of accreditation standards across disciplines. The Interprofessional Education Collaborative (IPEC) established IPE competencies in 2009, but evaluating how activities link to competencies has not been investigated in depth. The purpose of this project is to investigate how well two IPE activities align with IPEC competencies. To evaluate how our IPE a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…As suggested by West, et al (2015) that the IPE activities should be varied from learning in a variety of IP settings is optimal. Most of the studies applied practiced based learning in the hospital, clinic, and community, or some mentioned it as initial clinical experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As suggested by West, et al (2015) that the IPE activities should be varied from learning in a variety of IP settings is optimal. Most of the studies applied practiced based learning in the hospital, clinic, and community, or some mentioned it as initial clinical experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Despite a number of weaknesses, there was fairly common use of quasi-experimental research designs (pre-posttest) and mix-method design, which provided some indication of change associated with the delivery of IPE; where the study gathered two forms of data (survey and interviews), and there was a growing use of longitudinal studies to begin to establish the longer-term impact of IPE on education process, patients care and organizations change (Mast et al, 2015;West et al, 2015). Most reviews found that the outcome of their studies reported positive learner reactions, where most of the learners stated that the IPE brings value and new experience.…”
Section: Implication Of Implementing Ipementioning
confidence: 99%
See 2 more Smart Citations
“…However, much of the literature focuses on curricula delivery, content modalities, and measurement for pre/post course performance based on attitude changes and or readiness, and does not specifically direct content to attach meaning to the words or to explicate why competencies might need to exist. [21][22][23][24][25][26][27] By contrast, the literature was reviewed to discover what may be the underpinnings, constructs or definable mechanisms that support content development for the sub-competencies of IPEC's roles and responsibilities. Further, the literature from disciplines outside of the traditional health professions' cadre, were explored, with an emphasis on those factors that focus on what affects and drives human behavior and interaction within a professional context.…”
Section: Review Of the Literaturementioning
confidence: 99%